BETWEEN CUPS AND LIFE: ABSURDITY IN THE SHORT STORY PHILOSOPHY OF COFFEE BY DEE LESTARI - Waluyo, Prapto; Yusar, Dedi; Rustandi, Yuyus (Jurnal Salaka : Jurnal Bahasa, Sastra, dan Budaya Indonesia, 2025)
Dee Lestari's short story Filosofi Kopi (The Philosophy of Coffee) not only tells the story of Ben and Jody's journey in building a coffee shop, but also delves into the existential meaning and absurdity of life. This study explores the absurdity of the philosophical journey through an existentialist approach in Filosofi Kopi. Coffee in this story is positioned as a symbol of Ben and Jody's struggle to face the duality of idealism and pragmatism, specifically Ben's obsession with coffee perfection and Jody's pragmatic view, oriented toward profit. The analysis reveals that the absurdity of perfection, shaken by the presence of Twix coffee, prompts both characters to engage in a profound reflection on the meaning and purpose of life. Ben realizes that perfection lies not only in complexity but also in authenticity and the ability to touch the soul. Meanwhile, Jody begins to appreciate the profound philosophy embedded in coffee. Within the existentialist framework, Coffee Philosophy offers the perspective that humans can find harmony by accepting the absurdity of life and creating personal meaning.